Heroes of the valley - Stroud, Jonathan (Disney/Hyperion Books, 2009)
Halli Sveinsson, a mischievous young man who does not fit in with his peers and siblings, plays a trick on Ragnor that goes too far, forcing him to embark on a hero's quest in which he will face highway robbers, monsters, an intriguing girl, and truths about his family and the legends he grew up with.